(untitled) (Minerva. Revista de Filología Clásica, 2019)
Reseña de Alain M. Gowing, Empire and Memory. The Representation of the Roman Republic in Imperial Culture, Cambridge, Cambridge University Press, 2005, 178 págs. ISBN 13978-0-521-54480-1